Pendidikan Kesehatan dalam Pencegahan Diabetes Mellitus (DM) Dengan Makanan Sehat di Kota Samarinda: Pendidikan Kesehatan dalam Pencegahan Diabetes Mellitus (DM) Dengan Makanan Sehat di Kota Samarinda - bachtiar safrudin (Open Edutech Indonesia, 2025)
One of the nutritional problems in adolescents is the risk of diabetes mellitus (DM). The cause of DM is the consumption of unhealthy foods containing lots of calories that tend to be popular with adolescents. The impact of unhealthy food is weight gain or obesity as a determinant of DM. The results of a preliminary study showed that adolescents at the Jabal Husna Islamic Boarding School have a habit of consuming fast food, packaged drinks with sweeteners and rarely consume vegetables and fruits. The purpose of this community service is to provide knowledge about healthy foods and foods that have the potential to cause DM. The implementation of this PKM was carried out in January 2025 where the target was adolescents at the Jabal Husna Islamic Boarding School, Karang Asam Village, as many as 35 people. PKM activities include measuring TB and BB by interpreting BMI, health education about healthy foods, the risk of DM and the dangers of consuming unhealthy foods, conducting assessments by measuring pre- and post-test knowledge, related to adolescent knowledge about healthy foods and prevention of DM. The results of this PKM show an increase in adolescent knowledge from becoming. It is necessary to conduct scheduled health education by involving the person in charge of the Karang Asam Health Center program in providing education and regular check-ups on the health status of adolescents as a preventive effort to prevent DM among adolescents